Job Satisfaction, Psychological Contracts, and the Transition to Job Commitment in Outsourced Technology Staff - Venable, John; Thomson, Patricia (We-B Centre, School of Management, Edith Cowan University, 2003)
This paper focuses on developing an understanding of the factors that influence the development of job satisfaction, psychological contracts, and ongoing commitment to an organisation among outsourced personnel. A study was conducted in a very large IT services provider. It identifies additional (from those in the non-IT literature) factors specific to the IT industry that relate to job satisfaction, psychological contracts, and commitment to the organisation. It also proposes and provides evidence of progressive development of the ongoing commitment necessary for retention though successive stages of job satisfaction, psychological contract, and commitment to the employer organisation.